2019
DOI: 10.1186/s12902-019-0482-0
|View full text |Cite
|
Sign up to set email alerts
|

Insulin autoimmune syndrome induced by exogenous insulin injection: a four-case series

Abstract: BackgroundInsulin autoimmune syndrome (IAS) is a rare cause of hypoglycemia and is characterized by the presence of insulin autoantibodies. Patients with IAS usually complain of hypoglycemia without any previous insulin received. Glucocorticoids and immunosuppressants are used to treat IAS.Case presentationWe report four patients with diabetes who were diagnosed with non-classical IAS and describe the treatment of these patients. Moreover, the differential diagnosis with hyperinsulinism is discussed.Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(37 reference statements)
0
12
1
Order By: Relevance
“…Indeed, as mentioned above, it is rare for patients with IAs to manifest short-term drastic blood glucose fluctuations, 18 most of them tend to have hypoglycemia at night and hyperglycemia during the day. 19 Hyperinsulinemia is also one of the clinical manifestations of patients with IAs, 20 but their C-peptide and proinsulin levels may or may not increase. 21 In the present study, as our results are shown in Table 2 , the serum insulin levels of positive patients were just significantly higher than those of IA- patients at 0h and 2h, while no significant difference in C-peptide levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as mentioned above, it is rare for patients with IAs to manifest short-term drastic blood glucose fluctuations, 18 most of them tend to have hypoglycemia at night and hyperglycemia during the day. 19 Hyperinsulinemia is also one of the clinical manifestations of patients with IAs, 20 but their C-peptide and proinsulin levels may or may not increase. 21 In the present study, as our results are shown in Table 2 , the serum insulin levels of positive patients were just significantly higher than those of IA- patients at 0h and 2h, while no significant difference in C-peptide levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as mentioned above, it is rare for patients with IAs to manifest short-term drastic blood glucose fluctuations, 18 most of them tend to have hypoglycemia at night and hyperglycemia during the day. 19 Hyperinsulinemia is also one of the clinical manifestations of patients with IAs, 20 but their C-peptide and…”
mentioning
confidence: 99%
“…Such antibodies have been identified in over one‐third of Graves disease or chronic hepatitis patients 8 . The antibodies analysed in the present study are insulin‐binding immunoglobulins to endogenous or exogenous insulin, which can develop to bovine, porcine, human or human analogue insulins 9,10 . These differ from autoantibodies to insulin‐producing cells, such as anti‐GAD, ‐IA2 and ‐ZnT8, which are associated with propensity to develop T1D and often decline with increasing T1D duration.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Shen et al 35 found some evidence of high levels of insulin antibodies circulating in the blood of patients who had been diagnosed with diabetes mellitus and were being treated previously with exogenous insulin, potentially leading to a hyperinsulinemia–hypoglycemia state. Furthermore, a high insulin level in states of insulin resistance may result in hypertension due to insulin’s effect on the SNS with the release of catecholamines.…”
Section: Exogenous Hyperinsulinemia and Insulin Antibodymentioning
confidence: 99%